KONTEKSTUALISASI MISTERI KENOSIS ALLAH DALAM TEOLOGI ST. MONTFORT DAN KAITANNYA DENGAN PENERAPAN OMNIBUS LAW - Adon, Mathias Jebaru; Wotan, Fidelis Bolo; Riyanto, Eko Armada (Jurnal Lektur Keagamaan, 2024)
This research explores the role of theology in relation to socio-political challenges in Indonesia, particularly in light of the Omnibus Law Bill. The study draws on the theology of Kenosis as taught by St. Louis-Marie de Montfort, applying it to the contemporary Indonesian context. The Omnibus Law, favoring capital holders over workers, has prompted a call for the Indonesian Church to intervene. This study employs qualitative approach, relying on a literature review for data collection. The study finds parallels between the current situation in Indonesia and 17th-century France under Louis XIV, where Montfort developed the Theology of Kenosis in response to the king’s centralization of power and heavy taxation. The Theology of Kenosis, emphasizing leaders’ duty to serve their people, is found to be highly relevant to Indonesia today. The study concludes that this theological model can guide leaders in creating public policies that prioritize people’s welfare over corporate interests. This aligns with the principle of divine solidarity with humanity, particularly the poor. The application of Kenosis theology to the Omnibus Law could result in greater consideration for worker welfare, environmental sustainability, and the overall well-being of the Indonesian people.